The Application of Gestalt and Design Principles on Visual Based Games for Children - Noor Udin (Bina Nusantara University, 2017)
There are various visual games that we know, from puzzle, guess the picture, mix and match, and many more. Kids around the world play visual games because it is fun, imaginative, and stimulate their creativity. This research elaborates how visual games become more interested with the organization of visual elements through design principles and Gestalt theory. It proves that visualbased games are chosen by children and parents to develop their creativity and imagination.